PENGARUH MODEL KOOPERATIF TIPE THINK PAIR SHARE (TPS) TERHADAP HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN PENDIDIKAN PANCASILA DI KELAS V GUGUS II KECAMATAN KPGD KABUPATEN SOLOK SELATAN - Nurhaliza, Siti; Rafhi Febryan Putera (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The purpose of this research is to detail how the Pancasila Education learning results in fifth grade Cluster II at KPGD District, South Solok Regency were impacted by the Think Pair Share (TPS) cooperative model. Using a quantitative approach and a nonequivalent control group design kind of quasi-experimental methodology, this research was conducted. The experimental group averaged 83.50 on the posttest, while the control group averaged 74.71. This average posttest score clearly shows that the experimental group outperformed the control group. The hypothesis test yields t hitung = 3.6778, but t tabel is 2.056 at the 0.05 level of significance. Class V Cluster II students in KPGD District, South Solok Regency, were found to benefit significantly from using the Think Pair Share (TPS) cooperative model in their Pancasila Education lessons, leading us to accept H1 and reject H0.